Computed tomography findings of postoperative complications in lung transplantation - Hochhegger,Bruno (2009)
Due to the increasing number and improved survival of lung transplant recipients, radiologists should be aware of the imaging features of the postoperative complications that can occur in such patients. The early treatment of complications is important for the long-term survival of lung transplant recipients. Frequently, HRCT plays a central role in the investigation of such complications. Early recognition of the signs of complications allows treatment to be initiated earlier, which improves survival. The aim of this pictorial review was to demonstrate the CT scan appearance of pulmonary complications such as reperfusion edema, acute rejection, infection, pulmonary thromboembolism, chronic rejection, bronchiolitis obliterans syndrome, cryptogenic organizing pneumonia, post-transplant lymphoproliferative disorder, bronchial dehiscence and bronchial stenosis.